2019
DOI: 10.5607/en.2019.28.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD68/TGFβ Co-expressing Microglia/ Macrophages after Transient Middle Cerebral Artery Occlusion in Rhesus Monkeys

Abstract: The function of microglia/macrophages after ischemic stroke is poorly understood. This study examines the role of microglia/macrophages in the focal infarct area after transient middle cerebral artery occlusion (MCAO) in rhesus monkeys. We measured infarct volume and neurological function by magnetic resonance imaging (MRI) and non-human primate stroke scale (NHPSS), respectively, to assess temporal changes following MCAO. Activated phagocytic microglia/macrophages were examined by immunohistochemistry in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The impact of aging on the expression of TGF-β after stroke remains understudied. Microglia and monocyte-derived macrophages are thought to be major cellular sources of TGF-β within the brain after stroke (Yeo et al 2019). Previous studies have shown that TGF-β expression increases in the brain (Krupinski et al 1996) and blood (Jiang et al 2017) after stroke, leading to increased Smad signaling and reactive gliosis, which is further increased by aging (Doyle et al 2010;Cekanaviciute et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of aging on the expression of TGF-β after stroke remains understudied. Microglia and monocyte-derived macrophages are thought to be major cellular sources of TGF-β within the brain after stroke (Yeo et al 2019). Previous studies have shown that TGF-β expression increases in the brain (Krupinski et al 1996) and blood (Jiang et al 2017) after stroke, leading to increased Smad signaling and reactive gliosis, which is further increased by aging (Doyle et al 2010;Cekanaviciute et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The transient endovascular MCAO technique was applied as in our previous study [ 24 , 25 ]. An endovascular occlude was advanced over micro-guidewire (Synchro 14, Boston Scientific, Fremont, CA) and wedged in the distal M1 or superior M2 division branch of the right MCA under double fluoroscopic roadmap images.…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33][34] In our study, we found IBA1-positive microglia and CD68 and IBA1 double-positive cells increased in thalamus and cortex after irradiation. CD68 was recognized as microglial phagocytosis marker, 35,36 and increased microglia activity and neuroinflammation may contribute to gamma ray-induced brain lesion. 37 Indeed, several proinflammatory cytokines, such as IL-1β, IL-6, and TNF-α, appear to be involved in the brain's response to irradiation.…”
Section: F I G U R Ementioning
confidence: 99%